Language, Thought And Social Awareness: a Preliminary Anthropological Linguistic Investigation Of Time And Space in The Bima Language - Kamaludin Yusra (Antropologi Indonesia, 2016)
This article discusses the connection between language and thought processes and its implication towards social consciousness and attitudes. The framework is developed from various concepts of linguistic relativity particularly temporal and spatial deictic systems. Data were introspectively collected from the Bima native speakers selected based on dialectal variation, topography, and political geography and descriptively analyzed by identifying, classifying, describing and explaining the connection between various linguistic forms and spatio-temporal dimensions and social consciousness. The study finds that the concept of time in the language is not only semantically realized in adverbs of time but also morphologically represented in linguistic markers of present, past and future. Space is realized through the choice of three-dimensional locative markers: ‘ake’ speaker proximity, ‘ede’ hearer proximity, and ‘aka’ speaker-hearer distant detachment. Location is also marked by other factors: topography, geography, trans-communication pathways, and socio-political vitality of referred area. The study shows a strong relationship in both expert and commoner speakers’ understanding of spatial and temporal concepts although explicit reference to space and time as required in the language does not significantly materialize in different attitudes toward them.Key Words: language, thought, social awareness, deictic systems